2019
DOI: 10.1021/acs.jpclett.9b00608
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Theory of First-Order Prefreezing

Abstract: Prefreezing is the prewetting of the crystalline phase at the interface of a melt to a solid substrate via a first-order phase transition. We present a phenomenological theory of prefreezing and analyze thermodynamic properties of the prefrozen crystalline layer. The theory enables a clear thermodynamic explanation of the abrupt formation of a mesoscopically thick crystalline layer during cooling and defines the corresponding transition temperature as a function of the interfacial free energies. It is shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…The glass transition temperature of polycaprolactone is Tg1 = 213 K [ ( 45)] and the melting temperature Tm = 335 K [ ( 14) (19)]. The enthalpy coefficients ls of Liquid 1, gs of Liquid 2, and lg of Liquid 3 are determined using (4-9) and given in (18)(19)(20):…”
Section: -3 Application To Poly (-Caprolactone)mentioning
confidence: 99%
“…The glass transition temperature of polycaprolactone is Tg1 = 213 K [ ( 45)] and the melting temperature Tm = 335 K [ ( 14) (19)]. The enthalpy coefficients ls of Liquid 1, gs of Liquid 2, and lg of Liquid 3 are determined using (4-9) and given in (18)(19)(20):…”
Section: -3 Application To Poly (-Caprolactone)mentioning
confidence: 99%
“…Previous studies on adsorbed shorter alkanes, mainly in the length range 20 < n < 40, have found that monolayers on graphite melt at temperatures somewhat above the bulk melting point T m bulk , with additional phase transitions in the ordered state . A ″prefreezing″ effect was also found in PE and PCL thin layers on graphite and other substrates, where a thin layer of polymer is found to crystallize above its bulk melting point T m bulk (by 47 K for PE on MoS 2 ) at the substrate–melt interface. The effect is attributed to the reduced overall interface energy when a semicrystalline thin layer is sandwiched between the substrate and melt compared to that of a direct substrate–melt interface. Most notably, the melting of multilayers of n -C 60 H 122 and n -C 390 H 782 was reported to occur, respectively, 45 and 55 K above T m bulk , prior to our study on C 390 H 782 .…”
Section: Introductionmentioning
confidence: 95%
“…Note that when γ sm > γ sc + γ cm , the contact angle θ becomes zero and f (0) = 0 (Equation (4)), implying that the energy barrier for heterogeneous nucleation (∆G * het ) vanishes. Under this condition, crystallization can even take place above T m via prefreezing [3,[5][6][7][8][9], the other phenomenon of interface-induced crystallization, which is beyond the framework of classical nucleation theory. For heterogeneous nucleation, θ has a value 0 < θ < 180°and the function 0 < f (θ) < 1.…”
Section: Theorymentioning
confidence: 99%
“…In general, a solid substrate can induce the crystallization of liquids either by heterogeneous nucleation [1,2] or by prefreezing [3,4]. Prefreezing, i.e., the formation of a stable crystalline layer at the substrate interface above the melting temperature (T m ) of the material, is an equilibrium phenomenon and does not require a nucleation event [5][6][7][8][9]. By contrast, heterogeneous nucleation is an activated process taking place at a finite supercooling below T m [10].…”
Section: Introductionmentioning
confidence: 99%